Two novel amino acid-coated super paramagnetic nanoparticles at low concentrations label and promote the proliferation of mesenchymal stem cells. Issue 12 (26th January 2016) - Yu, Zhe-Zhen; Wu, Qing-Hua; Zhang, Shang-Li; Miao, Jun-Ying; Zhao, Bao- Xiang; Su, Le
Abstract : We identified two amino acid-coated magnetic nanoparticles that promoted mesenchymal stem cell growth without the need for transfection agents by increasing the proportion of cells in the S phase. Abstract : We identified two amino acid-coated magnetic nanoparticles that promoted mesenchymal stem cell growth without the need for transfection agents by increasing the proportion of cells in the S phase. Because of the low concentration, high labelling efficiency and promotion of cell growth, these two nanoparticles may be potential labelling biomaterials for cell tracking.